Alternatif Penyelesaian Waris Pengganti Di Indonesia - Ahmad Insya' Ansori; Moh Ulumuddin (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2019)
The difference between salaf scholars and modern scholars about the successor to successors. Salaf scholars state that "successor inheritance" does not exist, and with the principles of naqliyyah and ijma 'Companions, hold firm that the problem of "inheritance" is qat'i, ta'abbudi, not ta'aqquli, not ijtihadi, and they uphold ijma 'Companions because there is a basis for the words of the Prophet Muhammad about it. Whereas modern scholars (khalaf) in KHI and Hazairin thought stated that "successor inheritance" exists and has the inheritance rights of his parents who died, and they (modern scholars) put the issue of "successor inheritance" of zanni, ta'aqquli, and ijtihadi, for the sake of social benefit in Indonesia.